2019
DOI: 10.3390/medicina55070346
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physiological and Biochemical Autonomic Indices in Children with and without Autism Spectrum Disorders

Abstract: Background and objectives: Autism Spectrum Disorder (ASD) is a complex neuro-developmental disorder and it has been suggested that symptoms of ASD are associated with neural networks that regulate the Autonomic Nervous System (ANS). However, the nature of autonomic atypicalities in ASDs remain largely unknown. Measures like Heart Rate Variability (HRV) and urinary Vanillylmandelic Acid (VMA) estimation are sensitive and non-invasive physiological and biochemical indicators of autonomic nervous activity. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The STV and HF (ln) of male Sal, male VPA, and female Sal mice were significantly increased from 4 to 8 weeks of age, whereas these of female VPA mice remained unchanged, suggesting the strong suppression of parasympathetic nervous development in female VPA mice. Several reports revealed that the assessment of the sympathetic and parasympathetic activity using HRV in children with ASD yielded inconsistent results [25][26][27]48 . As ASD is a heterogeneous disease 1 , it can be inferred that such diversity occurred because of the characteristics of the population and the environmental factors that were involved in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…The STV and HF (ln) of male Sal, male VPA, and female Sal mice were significantly increased from 4 to 8 weeks of age, whereas these of female VPA mice remained unchanged, suggesting the strong suppression of parasympathetic nervous development in female VPA mice. Several reports revealed that the assessment of the sympathetic and parasympathetic activity using HRV in children with ASD yielded inconsistent results [25][26][27]48 . As ASD is a heterogeneous disease 1 , it can be inferred that such diversity occurred because of the characteristics of the population and the environmental factors that were involved in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Maturation of autonomic responses occurs throughout gestation ( 35 ) ( 36 ) and in the neonatal period ( 37 ) ( 38 ), with a shift from more sympathetic to more parasympathetic drive. Autonomic imbalance occurs in a variety of pathologic conditions and has been reported in children with ASD ( 16 ) ( 18 ) ( 20 ) ( 21 ) ( 22 ) ( 23 ) ( 25 ). Some studies have reported a slightly higher HR in children with ASD compared to typically developing children, especially during certain activities or phases of sleep ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Children with ASD have been reported to have differences in HR patterns compared to neurotypical individuals, including higher HR ( 16 ) ( 17 ). The mechanism of these findings is not well understood, but there is some evidence of overactive sympathetic tone ( 18 ) ( 19 ) ( 20 ) and decreased parasympathetic or vagal tone ( 21 ) ( 22 ) ( 23 ) ( 24 ) ( 25 ). These HR differences have particularly been noted during sleep and in response to social and non-social stimuli ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…31 The healthy children showed physiological flexibility which may be helpful for acute stress adaptation in healthy children and impaired in autism children. 32 The poor adaptation is associated with dysregulation of the autonomic activity, particularly sympathetic and parasympathetic outflow that outflows via brainstem and sacral spinal region. In the present study, sacrum showed high level of energy in children with autism compared to normal healthy.…”
Section: Discussionmentioning
confidence: 99%